Lateral Leadership: methodology to transform educational management (Revista Electrónica REDINE, 2025)
The underlying dynamics in the country's educational centers is a binding element with globalization and scientific advances. Likewise, 21st century society demands to transform educational management to contextualize it with global reality. Hence, the relevance of adopting managerial styles oriented to collaboration, assertive communication and participation. Therefore, lateral leadership constitutes an ideal management model to implement in Venezuelan schools, because it allows cooperation between agents belonging to the same technical-operational level. Accordingly, the present essay aimed to analyze lateral leadership as a methodology to transform educational management. It was supported by theoretical foundations from Pascual (2025), Arias (2024), Adler (2021) and Fisher and Sharp (1999). From a methodological point of view, the essay is part of a doctoral research in development, guided by the interpretive paradigm, a qualitative documentary approach based on the review of information and content analysis as a technique, an interview script and field notes recorded by the researcher were used as instruments. It should be noted that this methodology is accompanied by a descriptive-reflective process aimed at implementing new technical-administrative procedures in educational institutions, directly linked to the five-dimensional approach of research and, in this way, maintaining correspondence with the managerial processes that the knowledge society demands. Its author concludes that it is necessary to include in educational management a non-conventional managerial style, such as lateral leadership, because it allows transforming educational administration. Likewise, the applicability of collaboration between agents belonging to the same management level improves the response of the school organization, being an innovation in the spectrum of the educational system.
Keywords: collaboration; management teams; educational management; lateral leadership; educational organizations